A Multi-Level DC-DC Converter Configuration for PV Applications - Ghaderi, Davood (Ieee, 2019)
In this study, a novel method is presented for DC-DC boost converter design using PI controller's blocks. This approach reinforces the same voltage source by using two or more cascaded boost converter blocks simultaneously and is very effective in power transmission in renewable energy, resources where they produce a limited amount of power. In this converter, output voltage and current ripples are in a very low and acceptable level. The long-life is one advantage of using this circuit compared to conventional boost converters by considering the input current division at the input blocks. This structure provides us a multi-level output circuit. For example, with applying different duty cycles for blocks we can get different values of voltages in output and if we need to Time-varying voltages in different timescales, this structure can be useful. Two or more PI blocks control voltage production confronting rapid load changes by duty cycle changing and drive MOSFETs and restrict output voltage ripple. Simulation for the proposed configuration has been done by MATLAB/SIMULINK and results are confirming the mathematical analysis.
11th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 28-30, 2019 -- Bursa, TURKEY
Keywords: [No Keywords]